2022
DOI: 10.7554/elife.80282
|View full text |Cite
|
Sign up to set email alerts
|

Fat body phospholipid state dictates hunger-driven feeding behavior

Abstract: Diet-induced obesity leads to dysfunctional feeding behavior. However, the precise molecular nodes underlying diet-induced feeding motivation dysregulation are poorly understood. The fruit fly is a simple genetic model system yet displays significant evolutionary conservation to mammalian nutrient sensing and energy balance. Using a longitudinal high sugar regime in Drosophila, we sought to address how diet-induced changes in adipocyte lipid composition regulate feeding behavior. We observed that subjecting ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 101 publications
1
11
0
Order By: Relevance
“…Since our observations support a model where Act5C is required for FB Lpp secretion, perturbation of this process may explain (at least in part) the reduced LD and TG storage defects observed in Act5C-depleted FB tissues. This may also account for the reduced insulin signaling in Act5C-deficient FBs, as Lpp trafficking to the brain and insulin secretion from brain IPCs have been shown to directly correlate in other studies ( Brankatschk et al, 2014 ; Kelly et al, 2022 ).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Since our observations support a model where Act5C is required for FB Lpp secretion, perturbation of this process may explain (at least in part) the reduced LD and TG storage defects observed in Act5C-depleted FB tissues. This may also account for the reduced insulin signaling in Act5C-deficient FBs, as Lpp trafficking to the brain and insulin secretion from brain IPCs have been shown to directly correlate in other studies ( Brankatschk et al, 2014 ; Kelly et al, 2022 ).…”
Section: Resultsmentioning
confidence: 85%
“…Past work has shown that Lpp particles accumulate at neurons that harbor insulin-like peptides and influence their release ( Brankatschk and Eaton, 2010 ). More recent studies reveal that high sugar Drosophila feeding promotes Lpp-mediated crosstalk with the brain and ultimately influences insulin signaling and feeding behavior ( Kelly et al, 2022 ). A key emerging question is how Lpp lipid trafficking influences inter-organ insulin signaling and feeding, and how this impacts organismal homeostasis and development.…”
Section: Resultsmentioning
confidence: 99%
“…This relationship likely involves PC as well because a decrease in the ratio of PC:PE has been shown to increase insulin signaling ( 130 ). Additionally, Drosophila with Pect deficiency (the analog of PCYT2 ), develop insulin resistance and have a disrupted hunger response ( 131 ). This impact of PE on insulin signaling has also been demonstrated by our studies on Pcyt2 knockout mice.…”
Section: Pe Functions In the Cellmentioning
confidence: 99%
“…22 Since then, several other groups have adopted the system and used it to address different biological questions including rhythmic feeding and metabolic homeostasis. 18,[23][24][25][26][27][28][29][30][31][32] Available options of software to analyze locomotor activity from DAMS have multiplied over the years, offering different user interphases and developed in different coding languages [33][34][35][36][37] (summarized in Cai et al 15 ). In contrast, due to its recent implementation, user-friendly tools to analyze FLIC data are still scarce, 23 and available scripts require the user to understand and use R coding syntax.…”
Section: Introductionmentioning
confidence: 99%